Land use rights, market transitions, and labor policy change in China (1980-4) - Yiu-por Chen (Institute for the Study of Labor (IZA), 2012)
This paper provides a systematic analysis of the way shifts in property utilization rights in China induced another sequence of institutional changes that led to the rise of rural-urban labor migration from 1980 to 1984, a critical period in the country's market transition. I show that the 1980s' Household Responsibility System (HRS), which brought family farming back from the communal system, endowed rural households not only with land use rights, but also with de facto labor allocation rights. These shifts in property relations promoted a growth in agricultural market size as well as the emergence of intraprovincial non-hukou rural-urban migration, which may have made labor retention policies such as the small township strategy ineffective, and may have given the government an incentive to deregulate its subsequent labor market policy.
urn:nbn:de:101:1-2012081412461
Keywords: J43; J61; R23; R52; R58; 330; rural-urban migration; labor mobility; undocumented labor; institutional change; Bodenrecht; Landflucht; Arbeitsmobilität; Institutioneller Wandel; Arbeitsmarktpolitik; Übergangswirtschaft; China